2020
DOI: 10.1016/j.psj.2020.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of delayed feeding post-hatch on expression of tight junction– and gut barrier–related genes in the small intestine of broiler chickens during neonatal development

Abstract: The gut not only plays a key role in digestion and absorption of nutrients but also forms a physical barrier and first line of defense between the host and the luminal environment. A functional gut barrier (mucus and epithelial cells with tight junctions [ TJ ]) is essential for optimal health and efficient production in poultry. In current broiler system, chicks are deprived of food and water up to 72 h due to uneven hatching, hatchery procedures, and transportation. Post-hatch feed del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 86 publications
(120 reference statements)
0
37
0
Order By: Relevance
“…Since the gut microbiota affects SI structure and function (Dobrowolski et al, 2019), the timing of microbial introduction by external feed may also play a critical role in shaping the SI epithelium. Although previous studies have demonstrated the effect of the timing of first feeding of chicks on growth, nutrient utilization, metabolic pathways, gut integrity, and immunity (Bigot et al, 2003;Bar Shira et al, 2005;de Jong et al, 2017;Hicks et al, 2019;Payne et al, 2019;Proszkowiec-weglarz et al, 2020), no study has shown the effects on crypt and villi epithelial cell sub-types, involved in cellular turnover and intestinal functionality. Our study is the first to show the effect of the timing of first feeding on the quantities and proportions of stem, progenitor, proliferating, and differentiated SI epithelial cells, through immunofluorescence and histochemical of specific cell sub-type markers.…”
Section: Age (Days)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the gut microbiota affects SI structure and function (Dobrowolski et al, 2019), the timing of microbial introduction by external feed may also play a critical role in shaping the SI epithelium. Although previous studies have demonstrated the effect of the timing of first feeding of chicks on growth, nutrient utilization, metabolic pathways, gut integrity, and immunity (Bigot et al, 2003;Bar Shira et al, 2005;de Jong et al, 2017;Hicks et al, 2019;Payne et al, 2019;Proszkowiec-weglarz et al, 2020), no study has shown the effects on crypt and villi epithelial cell sub-types, involved in cellular turnover and intestinal functionality. Our study is the first to show the effect of the timing of first feeding on the quantities and proportions of stem, progenitor, proliferating, and differentiated SI epithelial cells, through immunofluorescence and histochemical of specific cell sub-type markers.…”
Section: Age (Days)mentioning
confidence: 99%
“…Research shows that delayed first feeding in chicks disrupts SI development by limiting crypt depths and villus heights, altering epithelial proliferation patterns, dysregulating differentiation-associated genes, and disrupting mucin dynamics (Geyra et al, 2001(Geyra et al, , 2002Uni et al, 2003a, de Jong et al, 2017. Long-term systematic effects of delayed first feeding include impaired nutrient utilization, altered regulation of metabolic pathways, disrupted barrier functions, and impaired gut immunity, all of which jeopardize animal welfare, impair performance in increase mortality rates (Bigot et al, 2003;Bar Shira et al, 2005;de Jong et al, 2017;Hicks et al, 2019;Payne et al, 2019;Proszkowiec-weglarz et al, 2020). In this study, we aimed to evaluate how the timing of first feeding of chicks influences the quantities and distribution of specialized SI epithelial cell sub-types during the initial 10 days post-hatch.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that age as well as environmental factors do influence the gut barrier in chicken [ 25 , 43 , 44 ]. In broiler chicken, the commencement of feed intake after hatch promotes intestinal development [ 24 , 45 ]. Especially in the small intestine, epithelial surface is constantly increasing due to villi enlargement and epithelial cell proliferation [ 46 ].The present study revealed a highly significant increase in the mRNA expression of the potentially pore-forming claudins 7 and 10 as well as of OCLN, MD2 and ZO1 in jejunum during that period.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained for CLDN1, CLDN5, ZO1 and OCLN in a recent study of Proszkowiec-Weglarz et al . 2020, in which expressional changes of different intestinal developmental markers were observed in the small intestine of broiler chicks fed immediately after hatch or deprived from food for 48h [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation